1991
DOI: 10.3168/jds.s0022-0302(91)78233-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bovine Somatotropin on Physiologic Responses of Lactating Holstein and Jersey Cows During Hot, Humid Weather

Abstract: Thirty-one lactating Holstein and Jersey cows were used to determine the effects of daily injections of 0 or 20 mg of recombinant bST on physiologic responses during hot, humid weather. Body temperature was determined by measuring milk temperature at each milking. Jugular blood was sampled for serum analysis of selected hormones, blood metabolites, and fatty acids, and arterial blood was sampled for blood pH and blood gas analysis. Milk was characterized for fatty acid composition. Blood pH was unchanged, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
7
14
1
4
Order By: Relevance
“…In the present study in both groups, milk yield was increased by rbST which accompanied with increases in both RT and RR throughout the experimental periods. The observation for an increase in heat production during rbST supplementation agrees with the reports of West et al (1991) and West (1994) that rbST-treated cows can increase heat production in a hot environment either high or lower milk producing cows.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present study in both groups, milk yield was increased by rbST which accompanied with increases in both RT and RR throughout the experimental periods. The observation for an increase in heat production during rbST supplementation agrees with the reports of West et al (1991) and West (1994) that rbST-treated cows can increase heat production in a hot environment either high or lower milk producing cows.…”
Section: Discussionsupporting
confidence: 81%
“…The concentrations of FFA in milk were significantly increased by supplemental rbST in cooled and non-cooled cows (Table 7). A similar result for an increase in milk fat content due to prolonged administration of rbST has also been observed previously (West et al, 1991;Chaiyabutr et al, 2000b). It has been known that milk fat is synthesized from fatty acids of both blood lipids and from de novo synthesis within the mammary epithelial cells.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, with respect to hormones, the concentrations of insulinlike growth factor (IGF-I) have been observed to increase after rbST administration (Ronge and Blum, 1989), but the rbST-IGF axis seems strictly dependent on the cow's nutritional status (Burton et al, 1994;Ronge et al, 1988). Insulin increments due to rbST treatment were also observed (Ronge and Blum, 1989;West et al, 1991), while other authors showed variable insulin changes after rbST treatment (Davis et al, 1988;de Boer and Kennelly, 1989;French et al, 1990). Many other authors have reported small changes of insulin and thyroid hormone concentrations (Butterwick et al, 1989;Chilliard et al, 1989;Cissé et al, 1991), and Johnson et al (1991) observed a significant reduction of 3,5,3'-triiodothyronine (T3) and cortisol concentrations.…”
Section: Introductionmentioning
confidence: 78%
“…Dentro de cada grupo de animais, a temperatura do leite apresentou aumentos significativos (P<0,05) entre os períodos da manhã e da tarde, com diferenças médias de 1,3ºC para os animais tratados e 1,1ºC para o grupo controle. WEST et al (1991) observaram que vacas Holandesas (n=6) e Jersey (n=8) tratadas com bST e mantidas em temperaturas de 22 a 35ºC (72% UR) apresentaram aumentos (P<0,01) de 0,3 a 0,6ºC na temperatura do leite em relação aos grupos controle. Dado que o número de animais no citado experimento foi semelhante ao utilizado no presente trabalho, a uniformidade do rebanho e, conseqüentemente, menor variabilidade dentro dos grupos tratados e controle provavelmente influenciaram os resultados dos testes estatísticos.…”
Section: Parâmetros Fisiológicos (Temperatura Do Leite E Temperatura unclassified